PENGARUH SERVQUAL TERHADAP KEPUASAN YANG BERDAMPAK PADA LOYALITAS PENGGUNA E-WALLET (OVO) - Foster, Bob (BISMA: Jurnal Bisnis dan Manajemen, 2020)
The purpose of this study is to analyze the direct effect of service quality on satisfaction, the direct effect of service quality and satisfaction on loyalty, the direct effect of satisfaction on loyalty, and the indirect effect of service quality on the loyalty of the users of e-wallet or digital wallet application (Ovo). The research sample consisted of 100 respondents taken by convenience random sampling technique. This research used a descriptive verification method. Data were analyzed using structural equation modeling run by Lisrel 8.80 software. The results showed that service quality and satisfaction had a positive and significant effect on loyalty, service quality had a positive and significant effect on satisfaction, and service quality had a positive and significant effect on loyalty as mediated by satisfaction. These results indicate that increasing service quality will increase consumer satisfaction, which finally increases consumer loyalty. Keywords: loyalty, satisfaction, service quality